N,N′-(Phenyliminodimethylene)diprop-2-enamide hemihydrate - Tamilvendan, Dhanapal (International Union of Crystallography, 2009)
In the title compound, C(14)H(17)N(3)O(2)·0.5H(2)O, the asymmetric unit consists of an N,N′-(phenyliminodimethylene)diprop-2-enamide molecule and one half-molecule of water, with the O atom of the latter having 2 site symmetry. The supramolecular architecture is framed by the interplay of two-dimensional networks of both O—H⋯O and N—H⋯O interactions supported by C—H⋯O and edge-to-face C—H⋯π interactions.